Professional development of specialists of preschool educational establishments to educationally-health activity on the basis of pedagogical management. - Makovetskaya N.V (Kharkov National Pedagogical University, 2011)
Priority directions modernization of activity of preschool educational establishments are shown. The analysis of publications, devoted creation of terms for educationally-health activity, and also professional development of specialists on its organization is resulted. In this connection light up possibilities of the use of pedagogical management. The value of management of the first and second levels is certain in professional development of specialists of preschool educational establishments. The types of organizational structures of management preschool educational establishment are appraised.